2012
DOI: 10.1002/tox.21777
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]pyrene modulation of acute immunologic responses in red Sea bream pretreated with lipopolysaccharide

Abstract: The effects of polycyclic aromatic hydrocarbons (PAHs) have been reported to modulate the immune response in aquatic animals, but the collected information of their effects on fish immunity is so far ambiguous. This study demonstrated that Benzo[a]pyrene (BaP) exposure altered the expression pattern of an antimicrobial peptide hepcidin (PM-hepc) gene and the activities of some immune-associated parameters in the lipopolysaccharide (LPS)-challenged red sea bream (Pagrus major). It was observed that LPS could in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…) and red sea bream (Bo et al . ). The immunomodulating activity of non‐viable bacteria may be due to the existence of certain microbial components, such as capsular polysaccharides, peptidoglycans and lipoteichoic acids, which are potent stimulators of the piscine immune system (Secombes et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and red sea bream (Bo et al . ). The immunomodulating activity of non‐viable bacteria may be due to the existence of certain microbial components, such as capsular polysaccharides, peptidoglycans and lipoteichoic acids, which are potent stimulators of the piscine immune system (Secombes et al .…”
Section: Discussionmentioning
confidence: 97%
“…LPS was considered as able to enhance antibacterial capacity by increasing lysozyme activity in red sea bream, Pagrus major (Temminck & Schlegel) (Bo et al . ). Nayak et al .…”
Section: Discussionmentioning
confidence: 97%
“…Similar stimulating effects of LPS on lysozyme activity and lysozyme mRNA were reported in Atlantic salmon (Salmo salar L.) (Paulsen et al 2003). LPS was considered as able to enhance antibacterial capacity by increasing lysozyme activity in red sea bream, Pagrus major (Temminck & Schlegel) (Bo et al 2012). Nayak et al (2008) also indicated the increase in serum lysozyme activity after injection of LPS (1 EU) in Indian carp, Labeo rohita (Hamilton) and its decrease at higher concentrations (10 and 20 EU).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Most of them are electrophilic compounds that have high activity, can interact with macromolecules in living bodies (e.g., proteins and nucleic acids), and have strong genotoxicity and immunotoxicity (Carlson et al 2002). BaP can cause oxidative stress by inducing a high level of reactive oxygen species (ROS), which could be related to cellular damage and apoptosis (Bo et al 2012), and it can also cause embryo toxicity and immunoa Corresponding author: jerrylee200224@126.com modulation in both invertebrates and vertebrates (Gopalakrishnan et al 2009). …”
Section: Introductionmentioning
confidence: 99%